Predicting Factors of Discharge Readiness in Patients with Sepsis - Prasiriputtipong, Honghem; Sripasong, Sarinrut; Danaidutsadeekul, Suporn; Rongrungreung, Yong (Journal of The Royal Thai Army Nurses, 2025)
This research is a study of predictive factors of frailty, uncertainty in illness, perceived disease severity, and the quality of discharge teaching with discharge readiness in patients with sepsis. The sample consisted of 107 sepsis patients admitted for inpatient treatment at a tertiary hospital in Bangkok. Data were collected using a demographic questionnaire, the Short-Form Discharge Readiness Scale, a short-form quality of discharge teaching scale, a perceived severity perception questionnaire, a short-form uncertainty in Illness scale for adults, and SHARE frailty index. Descriptive statistics and multiple regression analysis were used to analyze the data, with a significance level set at .05. The results indicated that 63.3% of the participants were ready for hospital discharge. The predictive factors collectively explained 8.3% of the variance in discharge readiness. Statistically significant predictors of discharge readiness included the quality of discharge teaching (ß = .848, p < .05) and perceived disease severity (ß = .080, p < .05). Healthcare professionals should provide dedicated pre-discharge education or develop programs to enhance discharge teaching. Additionally, assessing patients’ perceived disease severity is crucial in sepsis patients to ensure adequate discharge readiness.